Beyond trade: economic sanctions and their impact on the components of GDP - Zimmerman, Reid (2019)
Economic sanctions have become a favored instrument in the foreign policy toolbox for their ability to accomplish strategic objectives while averting the costs of warfare. Despite their frequent use, the economic consequences of sanctions on the target economy remain perplexing to both scholars and policymakers alike. While most empirical studies analyze the effects of economic sanctions on bilateral trade, our paper assesses the impact of sanctions on GDP through its five principal components: imports, exports, consumption, government expenditure, and investment. Using a fixed effects model, we uncover how economic sanctions modestly affect the target country’s imports, exports, and consumption; and show how additional factors such as the involvement of the United States or supranational institutions, as well as the political regime of the target country, influence our results.